The Effect of Language Experience Approach on Students' Comprehension in Reading Recount Text - Lukman Hakim (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The effect of language experience approach on students’ comprehension in reading recount text (A study at the etnth grade students of SMA Negeri 1 Sibabangun). The aim of this research is to know: 1) The extent of the application of language experience approach on students’ comprehension in reading recount text, 2) The extent of the students’ comprehension in reading recount text before and after using language experience approach, and 3) Whether there is a significant effect of language experience approach on students’ comprehension in reading recount text. The population of this research is all the tenth grade students which are divided into seven classes and total are 193 students. The sample is using systematic sampling is 32 students. This study is carried on by using experimental method. The data is collected by giving observation and test. The writer uses statistic processes in analyzing data by using formula of ttest. After collecting the data, it is found that the application of Language Experience Approach on students’ comprehension in reading recount text is 3.6. It is categorized “Very Good”. The students’ comprehension in reading recount text before using Language Experience Approach is 79.06. It is categorized “Good”. The students’ comprehension in reading recount text after using Language Experience Approach is 83.91. It is categorized “Very Good”. The calculation of ttest formula is 10.08, meanwhile the score of the ttable 5% significant level is 2.04. It is found that t0 calculation is bigger than ttable (10.08 > 2.04). It showed Ha is accepted, it means that there is a significant effect of students’ comprehension in reading recount text before Language Experience Approach at the tenth grade students of SMA Negeri 1 Sibabangun. Keywords: Language Experience Approach, Reading, Comprehension, Recount.